Effect of Yeast Culture on Reproductive Performance, Gut Microbiota, and Milk Composition in Primiparous Sows - Zhizhuo Ma; Ze Wu; Yu Wang; Qingwei Meng; Peng Chen; Jianping Li; Anshan Shan (Animals, 2023)
The objective of this study was to evaluate the effects of yeast culture (YC) on reproductive performance, gut microbiota, and milk composition in primiparous sows. A total of 60 primiparous sows were randomly assigned to the control group (CON) and YC group (0.5% YC during gestation and 0.8% YC during lactation) consisting of 30 replicates, with one sow in each. The results showed that dietary YC supplementation increased the piglet birth weight and backfat thickness at 28 d of lactation (p < 0.05). Dietary YC supplementation increased the apparent total tract digestibility (ATTD) of gross energy and calcium during lactation, the content of acetic acid and propionic acid at 110 d of gestation, and the content of acetic acid and butyric acid at 28 d of lactation in feces (p < 0.05). Furthermore, dietary YC supplementation decreased the abundance of Firmicutes, Lachnospiraceae_XPB1014_group, and Terrisporobacter (p < 0.05), and increased the abundance of Prevotellaceae_NK3B31_group and Rikenellaceae_RC9_gut_group (p < 0.05). Compared to the control group, dietary YC supplementation increased the fat and lactose content of the colostrum (p < 0.05). Metabolomics analysis showed that YC increased 26 different metabolites in the colostrum. Among them were mainly pantothenic acid, proline, isoleucine, phenylalanine, acylcarnitine, and other metabolites. In conclusion, these results suggested that dietary YC supplementation improves reproductive performance and gut health and increases the nutrient content in the colostrum of primiparous sows.